Perception of Poverty and Overpopulation amongst the Rural Communities of Udayapur District, Nepal - Dhungel, Harka Bahadur; Ghimire, Sanjay (Baneshwor Campus Journal of Academia, 2025)
This study reflects the situation of poverty and overpopulation in the rural community of Udaipur district of Nepal. This study was conducted using a mixed research method. In order to identify the situation of poverty and high population in this district, the study has been completed by including a total of 300 rural households as a sample. Interviews were conducted with 30 participants as key informants for the study, while focus group discussions were conducted in 5 groups. The study concluded that poverty is basically the lack of employment, education, health services, and basic resources. Overpopulation appears as a major contributor to worsening poverty, food security, and environmental degradation. The major effects of growing population pressures identified by the respondents include land fragmentation, deforestation, and increased migration. Gender inequalities in poverty understanding appear along with inequalities in social structures, where women, Dalits, and indigenous people appear as major groups highly susceptible to poverty. Furthermore, the quantitative results indicate a significant positive relationship between the size of the household and the level of poverty because larger families are highly vulnerable to financial insecurity. Researchers have suggested various intervention programs in relation to policy formulation and/or implementation to address this issue, such as improvement in the educational system of rural communities, development of new family planning programs, and job opportunities through sustainable development programs. Lastly, this research study aligns with and relates to worldwide and local patterns of perceiving poverty in view of local issues like subsistence agriculture and the local effects of migration on developing economies like that of Nepal.